Whole‐genome analyses provide no evidence for dog introgression in Fennoscandian wolf populations. (9th November 2020) - Smeds, Linnéa; Aspi, Jouni; Berglund, Jonas; Kojola, Ilpo; Tirronen, Konstantin; Ellegren, Hans
Abstract: Hybridization and admixture can threaten the genetic integrity of populations and be of particular concern to endangered species. Hybridization between grey wolves and dogs has been documented in many wolf populations worldwide and is a prominent example of human‐mediated hybridization between a domesticated species and its wild relative. We analysed whole‐genome sequences from >200 wolves and >100 dogs to study admixture in Fennoscandian wolf populations. A principal component analysis of genetic variation and Admixture showed that wolves and dogs were well‐separated, without evidence for introgression. Analyses of local ancestry revealed that wolves had <1% mixed ancestry, levels comparable to the degree of mixed ancestry in many dogs, and likely not resulting from recent wolf–dog hybridization. We also show that the founders of the Scandinavian wolf population were genetically inseparable from Finnish and Russian Karelian wolves, pointing at the geographical origin of contemporary Scandinavian wolves. Moreover, we found Scandinavian‐born animals among wolves sampled in Finland, demonstrating bidirectional gene flow between the Scandinavian Peninsula and eastern countries. The low incidence of admixture between wolves and dogs in Fennoscandia may be explained by the fact that feral dogs are rare in this part of Europe and that careful monitoring and management act to remove hybrids before they backcross into wolf populations.